Genome-wide association analysis of salt tolerance QTLs with SNP markers in maize (Zea mays L.) - Xie, Yonghong; Feng, Yan; Chen, Qi; Zhao, Feike; Zhou, Shuijuan; Ding, Ying; Song, Xianliang; Li, Ping; Wang, Baohua (Genes & genomics, 2019)
Background Salt-tolerant breeding of maize has great significance to the development and utilization of saline–alkaline soil and the maintenance of grain security. Genome-wide association study (GWAS) has been widely used in maize genetics and breeding. Objective To discover new salt-tolerant genes in maize by association analysis, which can provide technical supports for the innovation and genetic improvement of salt-tolerant germplasm resources in maize. Methods Totally 150 maize inbred lines were genotyped with a high-density chip. GWAS was carried out to identify the significant single nucleotide polymorphisms (SNPs) which were associated with maize salt tolerance. Totally 34,972 SNPs with high quality and diversity were selected from 56,110 SNP markers, which were distributed on 10 chromosomes of maize. The GLM algorithm in TASSEL5.2 was used to analyze the five traits related to salt tolerance. Results Using a strict LOD threshold of 4.5, totally 7 SNP loci were identified, which were significantly correlated with plant height change rate and fresh weight change rate. The high density fingerprints of 150 inbred lines were clustered by TASSEL5.2 software to construct genetic clustering map to estimate the genetic distance and the subgroups. The 150 maize inbred lines were divided into two groups: SS group and NSS group, and the SNP loci of the salt-tolerant index showed difference in chromosome distribution. Based on previous studies, we screened 8 candidate genes for salt tolerance in maize and four of them were further validated by real-time quantitative PCR. Conclusion Totally 7 SNP loci and 8 candidate genes related to salt tolerance in maize were identified, which will be of special value in molecular breeding of salt-tolerant maize.